Research across contexts and timescales with the experience sampling method: Applications in the study of language anxiety - Arndt, Henriette L.; Krstic, Osa Marie (Studies in Second Language Learning and Teaching, 2025)
Language anxiety (LA) is among the most researched emotions in language learning research. Mirroring the recent dynamic turn in the broader field, LA researchers are increasingly interested in the situation-specific and dynamic nature of anxiety (Elahi Shirvan & Taherian, 2021; MacIntyre, 2017). In practice, this must be accompanied by a movement towards methodologies sensitive to potential dynamic changes in LA within and across various contexts. The idiodynamic methodconstitutes one such approach, which allows researchers to investigate moment-to-moment changes in situated LA (e.g., MacIntyre & Gregersen, 2022; Macintyre & Legatto, 2011), whereas general self-report questionnaires implemented longitudinally typically capture changes at the level of weeks and months. However, quantitative studies on the intermediate timescales, at the level of hours and days, as well as those comparing LA across different contexts, remain comparatively rare. In this paper, we explore the potential of the experience sampling method (ESM; Csikszentmihalyi & Larson, 1987) as an approach to conducting longitudinal studies of LA in a variety of contexts at this timescale, within and beyond the language classroom. Drawing connections to recent theoretical and methodological developments, we reflect on how the ESM complements existing measures and provide practical guidance for researchers interested in integrating the method into their own studies.